2021
DOI: 10.1029/2020gl092069
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Clumped Isotope Thermometer Calibration (0.5–1,100°C) Using Carbonate‐Based Standardization

Abstract: The potential for carbonate clumped isotope thermometry to independently constrain both the formation temperature of carbonate minerals and fluid oxygen isotope composition allows insight into long‐standing questions in the Earth sciences, but remaining discrepancies between calibration schemes hamper interpretation of temperature measurements. To address discrepancies between calibrations, we designed and analyzed a sample suite (41 total samples) with broad applicability across the geosciences, with an excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
270
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(300 citation statements)
references
References 44 publications
26
270
4
Order By: Relevance
“…In addition, a reanalysis of samples from five previous calibrations by Anderson et al. (2021) using carbonate standardization revealed no significant differences in temperature dependence of Δ 47 between the different sample sets. This, solved a long standing debate about variations in slope among calibrations…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In addition, a reanalysis of samples from five previous calibrations by Anderson et al. (2021) using carbonate standardization revealed no significant differences in temperature dependence of Δ 47 between the different sample sets. This, solved a long standing debate about variations in slope among calibrations…”
Section: Introductionmentioning
confidence: 75%
“…These studies yielded statistically indistinguishable slopes and intercepts despite the use of independent sample sets and in the case of Peral et al (2018), a different analytical system. In addition, a reanalysis of samples from five previous calibrations by Anderson et al (2021) using carbonate standardization revealed no significant differences in temperature dependence of Δ 47 between the different sample sets. This, solved a long standing debate about variations in slope among calibrations A possible limitation of carbonate standardization is that available carbonates have a smaller range in δ 47 and, perhaps more importantly, a smaller range in Δ 47 values than what is achievable with heated and equilibrated gases.…”
Section: Nomenclature and Data Processingmentioning
confidence: 87%
See 1 more Smart Citation
“…Clumped isotope compositions for the analysed calcites and aragonites range from 0.580 to 0.609 (I-CDES 53 ; excluding separated diagenetic calcites from the apical area and spar cements), which correspond to temperatures ranging from 20.0 to 29.5 °C based on the Anderson et al 54 equation. Anderson et al 54 found that inorganic, and most biogenic, carbonates (including aragonite) show the same temperature dependence; thus, their equation can confidently be applied to reconstruct palaeotemperatures for aragonites and calcites. Reconstructed aragonite and calcite Δ 47 palaeotemperatures from the same belemnite are consistently within error of each other, and are in agreement with other biotic aragonites from the sample (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This, of course, is not a problem in itself, but the InterCarb results unambiguously demonstrate that these standardization uncertainties are both necessary and sufficient to explain the inter‐laboratory scatter observed in this large data set ( N = 5,329). Going one step further, it could be argued that the ongoing persistence of inter‐laboratory discrepancies in Δ 47 calibrations (Petersen et al., 2019) is due, at least in part, to largely ignored standardization errors (Anderson et al., 2021). Whatever the case, it seems likely that future comparisons between results obtained in different laboratories would greatly benefit from more accurate error estimates.…”
Section: Discussionmentioning
confidence: 99%